THE ANALYSIS OF BUGEMM PROGRAM AT SMA PLUS NEGERI 17 PALEMBANG - Fatiha, Emilda Sinar (JURNAL DIDASCEIN BAHASA, 2018)
ABSTRACT: The reading program, BUGEMM runs twice in one academic year in SMA Plus Negeri 17. It requires the students to write two different kinds of scientific research papers, English and Bahasa. This study attempted to knowBUGEMM program implementation, advantages, problems, and the factors prohibiting and supporting the program.356 students, 11 teachers, parents, and head master participated in this study. Qualitative data were employed to identify the natural settings, and phenomena occurred during the program. The data were collected by questionnaires, interview, observation, and documentation. The study resulted: (1) The program started from the socialization to the tenth grader, continued to the writing process during one semester, examination, and revision; (2) The advantages of the program were: cultivating the students’ reading and writing habit, critical thinking, and inhabiting them in doing research; (3) the problems were: the program which organized twice in a year, the writing system and conducting chapter IV; (4) Students’ speaking and writing skills were the teachers’ problems; and (5) Printer and books prohibiting the students whiles parents and facilitiation supporting the students. Keywords:implementation, BUGEMM program.